Preliminary studies on the organization and development of a hexactinellid sponge from a Mediterranean cave, Oopsacas minuta - Boury-Esnault, N.; Vacelet, J. (In: van Soest, R.W.M., van Kempen, Th.M.G. & Braekman, J.-C. (Eds), Sponges in Time and Space. (Balkema: Rotterdam): 1-515, 1994)
A dense population of the hexactinellid sponge, Oopsacas minuta, living in a Mediterranean cave with a stable water temperature (13-l4.5°C), is easily accessible by SCUBA. The genera organization of the tissue corresponds to other hexactinellids, with choanochambers lined with anucleate collar bodies which bud from subjacent choanoblasts. Both collar bodies and choanoblasts are wrapped in a thin pinacoderm (reticulum) containing phagosomes. Symbiotic thread-like bacteria are abundant in the mesohyl and, surprisingly, inside the collars of collarbodies. The cave population reproduces sexually all year round. Spermatogenic cysts derive from archaeocyte congeries. Oocytes contain numerous yolk and lipid granules. The larva has a rounded anterior pole with numerous lipid globules and a conical posterior pole containing large granular cells. Larvae in advanced stages have choanochambers Iined with anucleate collar bodies, but devoid of reticulum. Stauractine spicules of the larval skeleton are secreted inside spiculocytes which have the same general features as in demosponges. The flagellated cell layer covering the middle part of the larva surface is composed of large mononucleate cells that are multiflagellated rather than uniflagellated as found in other sponges and in other diploblasts. These flagellated cells are covered by an epithelium which is pierced by their flagella. The new term "trichimella" is proposed for the hexactinellid larva. During free life, the larva swims counter-c1ockwise with the rounded, reserve-rich poJe forward. Both in adult and in embryo, individualized cellular units are Iinked by dense junctions whose interpretation is still uncertain. They can be understood either as intrasyncytial occlusions or as intercellular junctions. These preliminary results suggest that the commonly accepted assumption that hexactinellid tissue is a continuous general syncytium needs further investigations.
Proceedings of the 4th International Sponge Conference